Measuring Party Institutionalization in Developing Countries: A New Research Instrument Applied to 28 African Political Parties - Matthias Basedau; Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2008)
The institutionalization of political parties is said to be important for democratic development, but its measurement has remained a neglected area of research. We understand the institutionalization of political organizations as progress in four dimensions: roots in society, level of organization, autonomy, and coherence. On this basis we construct an Index of the Institutionalization of Parties (IIP), which we apply to 28 African political parties. The IIP uses extensive GIGA survey and fieldwork data. Initial results reveal a more differentiated degree of institutionalization than is commonly assumed. In addition to illustrating overall deficits in party institutionalization, the IIP highlights an astonishing variance between individual parties and - to a lesser extent - between national aggregates. Further research on party institutionalization remains necessary, particularly regarding its causes and consequences. – – Die Institutionalisierung politischer Parteien wird als wichtiger Faktor für die Demokratieentwicklung bezeichnet, deren Messung wurde in der Forschung jedoch vernachlässigt. In diesem Artikel wird die Institutionalisierung politischer Organisationen als fortschreitende Verstärkung der Verwurzelung in der Gesellschaft, des Organisationsniveaus, der Autonomie und Kohärenz verstanden. Auf dieser Grundlage schlagen wir ein neues Messinstrument für die Institutionalisierung von Parteien vor. Dieser Index der Institutionalisierung von Partien (IIP) wird anschließend auf 28 afrikanische Parteien angewendet. Die Ergebnisse deuten darauf hin, dass die Institutionalisierung politischer Parteien in Afrika wesentlich differenzierter zu betrachten ist als bisher angenommen. Neben der Darstellung allgemeiner Defizite in der Institutionalisierung der Parteien enthüllt der IIP auch erstaunliche Unterschiede zwischen den einzelnen Parteien und untersuchten Ländern insgesamt. Zukünftige Forschung sollte sich besonders der Ursachen- und Wirkungsanalyse widmen.
Keywords: 300; political parties; sub-Saharan Africa; institutionalization; stability; legitimacy